Optimization of Temperature-Control Measures for Concrete Structures: A Case Study of the Sluice Project - Yaoying Huang (Advances in Civil Engineering)
Temperature control and crack prevention in sluice pier concrete is a key issue in the early design and construction period. Strong surface insulation may lead to cracks after formwork removal, while weak surface insulation may result in a high crack risk in the early age. The water-cooling measure may also cause severe cracks at a rapid cooling rate. Therefore, the optimum temperature control scheme should be comparatively studied against the alternatives. In this paper, we investigate crack prevention in sluice pier concrete as a multiple-factor system optimization problem and investigate an optimization method for temperature-control measures using the uniform design method and a neural network model. The minimum ratios for the internal and surface points of the sluice pier concrete are taken as inputs, and the corresponding combinations of temperature-control parameters based on the uniform design method are taken as outputs. Combined with a sluice project, the optimization method for the temperature-control measures is implemented. The analysis results show that internal pipe cooling combined with reasonable surface heat preservation measures should be employed, and a low concrete pouring temperature is more beneficial than a low cooling temperature and long duration for crack prevention in sluice pier concrete.